ANALYSIS OF THE INFLUENCE OF NON-PERFORMING CREDIT POLICIES ON CONVENTIONAL BANK FINANCIAL STABILITY IN INDONESIA - Nyimas Amanda Aulia; Kiagus Rachmad Kurniawansyah; Erika Amalia; Bagus Hidayat; Anggun Suseno; Elda Yanti; Tri Danela Marses; Abizar Markin; Muhammad Rizky Saputra (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
Credit risk is the risk that occurs when customers fail to fulfill their obligations to the bank, both principal and interest. (Risna Eka Peratiwi, 2018 )The non-performing loan policy is a step taken by a bank to overcome credit risks arising from bad or uncollectible loans. Financial stability is an important indicator in determining the financial soundness and continuity of a bank's operations. The purpose of this research is to examine and find out the influence of non-performing credit policy arrangements on financial stability, identify the factors that can influence non-performing credit policy arrangements on financial stability, and analyze how the strategy of the Financial Services Authority (OJK) increases the effectiveness of non-performing credit policies on financial stability in Commercial Banks in Indonesia. The results of this study indicate that non-performing credit arrangements have a significant influence on financial stability in conventional commercial banks in Indonesia, by implementing effective non-performing credit policies, banks can reduce the risk of non-performing loans, strengthen financial position and at the same time increase overall financial stability. . Several factors that are significant in setting non-performing loan policies include the quality of the bank's financial condition, the quality of a bank's risk management, and the development of the banking industry. As well as the research results show that OJK implements several strategies in its efforts to increase the effectiveness of a non-performing loan policy regulation. by implementing an effective non-performing credit policy, banks can reduce the risk of non-performing loans, strengthen their financial position and at the same time increase overall financial stability. Several factors that are significant in setting non-performing loan policies include the quality of the bank's financial condition, the quality of a bank's risk management, and the development of the banking industry. As well as the research results show that OJK implements several strategies in its efforts to increase the effectiveness of a non-performing loan policy regulation. by implementing an effective non-performing credit policy, banks can reduce the risk of non-performing loans, strengthen their financial position and at the same time increase overall financial stability. Several factors that are significant in setting non-performing loan policies include the quality of the bank's financial condition, the quality of a bank's risk management, and the development of the banking industry. As well as the research results show that OJK implements several strategies in its efforts to increase the effectiveness of a non-performing loan policy regulation. the quality of a bank's risk management, and the development of the banking industry. As well as the research results show that OJK implements several strategies in its efforts to increase the effectiveness of a non-performing loan policy regulation. the quality of a bank's risk management, and the development of the banking industry. As well as the research results show that OJK implements several strategies in its efforts to increase the effectiveness of a non-performing loan policy regulation.